2004
DOI: 10.1614/wt-03-123r3
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate Efficacy on Velvetleaf Varies with Application Time of Day

Abstract: Field and growth chamber experiments determined the efficacy of temporal glyphosate applications on velvetleaf. Glyphosate was applied postemergence to velvetleaf periodically before and during light and after dark. In 1999, glyphosate at 840 g ae/ha applied before sunrise and after midday provided 54 and 100% velvetleaf control, respectively. In 2000, glyphosate at 840 g/ha applied before sunrise, midday, and after sunset provided 69, 100, and 37% velvetleaf control, respectively. In the growth chamber, glyph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 14 publications
2
38
1
1
Order By: Relevance
“…A variação do ângulo foliar em função da hora do dia em algumas espécies provavelmente se deve a adaptação às diferentes condições de irradiância. Maior intensidade luminosa provoca incremento no ângulo foliar de determinadas espécies, fato que permite inclinação mais horizontal (WALTZ et al, 2004). A aplicação de glifosato ao meio-dia permitiu aumento de 31 % no controle de A. theophrasti em comparação aos períodos de baixa luminosidade (MOHR, SELLERS e SMEDA, 2007).…”
Section: âNgulo Foliarunclassified
“…A variação do ângulo foliar em função da hora do dia em algumas espécies provavelmente se deve a adaptação às diferentes condições de irradiância. Maior intensidade luminosa provoca incremento no ângulo foliar de determinadas espécies, fato que permite inclinação mais horizontal (WALTZ et al, 2004). A aplicação de glifosato ao meio-dia permitiu aumento de 31 % no controle de A. theophrasti em comparação aos períodos de baixa luminosidade (MOHR, SELLERS e SMEDA, 2007).…”
Section: âNgulo Foliarunclassified
“…Waltz et al (2004) reported control of velvetleaf with glyphosate in the field to be correlated with the air temperature at the time of herbicide treatment. However, we did not find a relationship between ambient air temperature and common lambsquarters control by glyphosate.…”
Section: Resultsmentioning
confidence: 99%
“…(McWhorter and Azlin 1978) and quackgrass [Elymus repens (L.) Gould] (Klevorn and Wyse 1984). A time of day effect on glyphosate efficacy has been observed in velvetleaf (Mohr et al 2007;Waltz et al 2004), common lambsquarters, common ragweed, foxtail species (Martinson et al 2002), and barnyardgrass in some studies (Mohr et al 2007) but not in others (Stewart et al 2009). Ambient air temperatures can also affect glyphosate efficacy, absorption, and translocation (Adkins et al 1998;Jordan 1977;Masiunas and Weller 1988;Reddy 2000;Sharma and Singh 2001;Tanpipat et al 1997).…”
mentioning
confidence: 99%
“…Studies in the field and in greenhouses showed that glyphosate applications during a period with higher photosynthesis rate (between 10:30 a.m. and the sunset) offered better control levels. This effect is related to the fact that, because it is a herbicide with systemic action, high photosynthesis rates increase the transportation of metabolites in the plant, allowing the increment of the glyphosate translocation (Waltz et al, 2004). Some weed species are less sensitive to glyphosate since they show lower herbicide translocation (Shaner, 2009;Galon et al, 2013).…”
Section: Circadian Clock and The Efficiency Of Herbicidesmentioning
confidence: 99%